Transformasi Kurikulum Pendidikan Islam Berbasis Literasi Digital : Upaya Membangun Mahasiswa Muslim yang Adaptif dan Visioner - Mujiyatun Mujiyatun; Irham Abdul Haris (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The transformation of the Islamic education curriculum based on digital literacy is an essential step to enhance student engagement in higher education learning. This study aims to examine the implementation of digital literacy in the Islamic education curriculum and its impact on the quality of learning. A qualitative approach was used, involving observation, interviews, and documentation. The findings show that although some Islamic higher education institutions have integrated technology into learning, challenges related to lecturer readiness, digital access inequality, and limited resources remain major obstacles. Students responded positively to digital-based learning, which provided easier access to study materials and facilitated online interaction. However, the digital access gap needs to be addressed promptly to create a more equitable learning experience. The implications of this study suggest the need for ongoing lecturer training, improved technological infrastructure, and curriculum policies that support more effective integration of digital literacy in Islamic higher education.